'Down to brass tacks' - TUC leaflet about industrial production, 1947 (front) (1947)
1947 1945-1960 "'Down to brass tacks' - TUC leaflet about industrial production, 1947 (front)" [T0352.jpg], 1947, Trades Union Congress This TUC leaflet about industrial production covers a range of post-war issues including Joint Production Committees, the American Loan, shortages of food and raw materials, immigration.